Hunted - Hearne, Kevin (Hearne, Kevin. Iron druid chronicles, 2022)
For someone who's been alive for two thousand years, Atticus O'Sullivan is a pretty fast runner. Good thing, because he's being chased by not one but two goddesses of the hunt - Artemis and Diana - for messing with one of their own. Dodging their slings and arrows, Atticus, Granuaile, and his wolfhound, Oberon, are making a mad dash across modern-day Europe to seek help from a friend of the Tuatha Dé Danann. His usual magical option of shifting planes is blocked, so instead of playing hide-and-seek, the game plan is . . . run like hell. Crashing the pantheon marathon is the Norse god Loki. Killing Atticus is the only loose end he needs to tie up before unleashing Ragnarok -- AKA the Apocalypse. Atticus and Granualie have to outfox the Olympians and contain the god of mischief if they want to go on living - and still have a world to live in.